Pore Chemistry of Metal–Organic Frameworks - Ji, Zhe; Wang, Haoze; Canossa, Stefano; Wuttke, Stefan; Yaghi, Omar M. (Advanced functional materials, 2020)
The pores in metal–organic frameworks (MOFs) can be functionalized by placing chemical entities along the backbone and within the backbone. This chemistry is enabled by the architectural, thermal, and chemical robustness of the frameworks and the ability to characterize them by many diffraction and spectroscopic techniques. The pore chemistry of MOFs is articulated in terms of site isolation, coupling, and cooperation and relate that to their functions in guest recognition, catalysis, ion and electron transport, energy transfer, pore‐dynamic modulation, and interface construction. It is envisioned that the ultimate control of pore chemistry requires arranging functionalities into defined sequences and developing techniques for reading and writing such sequences within the pores. Pore chemistry addresses the positioning of functional groups on framework backbones into the configuration of site isolation, coupling, and cooperation to achieve desired properties for specific applications. The precision acquired by reticular chemistry promises to craft functionality sequences extending to the entire pore space, reminiscent of the sophistication of protein pockets.